Chemical-mechanical polishing slurry composition and method for manufacturing semiconductor by using the same

KR103031248B1Active Publication Date: 2026-10-13SOULBRAIN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020210190905
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2026-10-13
Estimated Expiration
2040-10-26

Smart Images

  • Figure 112021152131695-PAT00001_ABST
    Figure 112021152131695-PAT00001_ABST
Patent Text Reader

Abstract

The present invention provides a chemical mechanical polishing slurry composition comprising cerium oxide particles and a solvent, wherein the cerium oxide particles have a primary particle size of 1 to 5 nm and a secondary particle size of 2 to 15 nm, and the surface of the cerium oxide particles contains Ce3+ and Ce4+. According to this, by increasing the proportion of Ce3+ on the ceria surface, a high oxide film removal rate can be maintained at a low content despite the small particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a chemical mechanical polishing slurry composition and a method for manufacturing a semiconductor device, and more specifically, to Ce on the surface of ceria through synthesis, unlike conventional cerium oxide particles. 3+ The present invention relates to a chemical mechanical polishing slurry composition that possesses a high oxide film removal rate at a low content despite small particle size by increasing the ratio of, and a method for manufacturing a semiconductor device using the same. Background Technology

[0003] As semiconductor devices become more diverse and highly integrated, finer pattern formation technologies are being used, and consequently, the surface structure of semiconductor devices is becoming more complex and the step heights of surface films are becoming larger. In the manufacturing of semiconductor devices, the chemical mechanical polishing (CMP) process is used as a planarization technology to remove step heights in specific films formed on a substrate. For example, it is widely used as a process for interlayer isolation (ILD) to remove excess insulating films deposited for interlayer insulation, as a process for planarizing insulating films for shallow trench isolation (STI) to insulate between chips, and as a process for forming metal conductive films such as wiring, contact plugs, and via contacts.

[0004] In the CMP process, the polishing speed, the flatness of the polished surface, and the degree of scratch occurrence are important and are determined by CMP process conditions, the type of slurry, and the type of polishing pad. High-purity cerium oxide particles are used in the cerium oxide slurry. Recently, there has been a demand to achieve even greater miniaturization of wiring in semiconductor device manufacturing processes, and polishing scratches generated during polishing have become a problem.

[0005] Conventional cerium oxide slurries use particles ranging in size from 25 nm to 200 nm. When polishing is performed, even if fine polishing scratches occur, it is not a problem as long as they are smaller than the conventional wiring width. However, this is becoming a problem at the current stage where continuous high-level wiring miniaturization is being achieved. In response to this problem, attempts have been made to reduce the average particle diameter of the cerium oxide particles. However, in the case of existing particles, reducing the average particle diameter lowers the mechanical performance, which leads to a problem where the polishing speed decreases.

[0006] Even if one attempts to control the polishing speed and polishing scratches by controlling the average particle diameter of cerium oxide particles in this way, it is very difficult to achieve the target level of polishing scratches while maintaining the polishing speed.

[0007] In addition, conventional chemical mechanical polishing slurry compositions contain cerium oxide particles, Ce 3+ Dae Ce 4+ While optimizing the ratio, it fails to present an optimized level of average particle diameter, and therefore, the Ce on the ceria surface 3+ There is a need for research on polishing slurries containing ceria particles that exhibit a high oxide film removal rate despite their small particle size by increasing the proportion of ceria. The problem to be solved

[0009] The present invention has been devised to solve the aforementioned problems, and one embodiment of the present invention provides a slurry composition for chemical mechanical polishing.

[0010] In addition, another embodiment of the present invention provides a method for manufacturing a semiconductor device comprising the step of polishing using the chemical mechanical polishing slurry composition.

[0011] However, the technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem

[0013] As a technical means for achieving the aforementioned technical problem, one aspect of the present invention is,

[0014] The apparatus comprises cerium oxide particles; and a solvent, wherein the cerium oxide particles have a primary particle size of 1 to 5 nm and a secondary particle size of 2 to 15 nm, and an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt% has an average light transmittance of 50% or more for wavelength light in the 450 to 800 nm range, and on the surface of the cerium oxide particles, Ce 3+ and Ce 4+ A chemical mechanical polishing slurry composition is provided, comprising, wherein the cerium oxide particles have two or more Raman peak spectra.

[0015] The above cerium oxide particles are 455 cm -1 to 460 cm -1 The first Raman peak, 587 cm within the band range -1 to 627 cm -1 The second Raman peak and 712 cm within the band range -1 to 772 cm -1 It can be characterized by having a third Raman peak spectrum within the band range.

[0016] The ratio A / B of the first Raman peak intensity (A) to the second Raman peak intensity (B) can be characterized as being 25 or less.

[0017] The ratio A / C of the first Raman peak intensity (A) to the third Raman peak intensity (C) can be characterized as being 50 or less.

[0018] Ce on the surface of the above cerium oxide particles 3+ It can be characterized by containing more than 30% of

[0019] The average primary particle size of the above cerium oxide particles may be characterized as being 1 to 10 nm.

[0020] An aqueous dispersion in which the content of the above-mentioned cerium oxide particles is adjusted to 1.0 weight% may be characterized by having an average light transmittance of 90% or more for wavelength light in the 800 nm region.

[0021] The above cerium oxide particles may be characterized by being included in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the total composition.

[0022] The above composition may be characterized by having a pH of 2 to 7.

[0023] The above solvent may be characterized as being deionized water.

[0025] In addition, another aspect of the present invention is,

[0026] A method for manufacturing a semiconductor device is provided, comprising the step of polishing using the above chemical mechanical polishing slurry composition. Effects of the invention

[0028] According to one embodiment of the present invention, Ce on the surface of ceria 3+ By increasing the ratio, it is possible to maintain a high oxide film removal rate at low content despite the small particle size.

[0029] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the invention or the claims. Brief explanation of the drawing

[0031] Figure 1 illustrates an oxide film removal mechanism according to one embodiment of the present invention. Figure 2a shows the XRD analysis results of cerium oxide particles prepared according to one embodiment of the present invention. Figure 2b compares the XRD analysis results of cerium oxide particles produced by the present invention and general cerium hydroxide particles. Figure 3a shows the Raman peak spectrum results of ceria particles manufactured to a size of 60 nm. Figure 3b shows the Raman peak spectrum results of cerium oxide particles prepared according to one embodiment of the present invention. FIG. 3c shows the results of comparing the Raman peak spectra of ceria particles manufactured with a size of 60 nm and cerium oxide particles manufactured according to one embodiment of the present invention. Figures 4a and 4b are TEM / SEM images of cerium oxide particles according to one embodiment of the invention. FIG. 4c shows the results of the Malvern Zerasizer (DLS method) of cerium oxide particles according to one embodiment of the invention, showing the results of the secondary particle size. FIG. 5a shows the results of the light transmittance analysis of cerium oxide particles according to one embodiment of the present invention. FIG. 5b shows the results of an analysis of light transmittance according to wavelength of cerium oxide particles according to one embodiment of the present invention. Specific details for implementing the invention

[0032] The present invention will be described in more detail below. However, the present invention may be implemented in various different forms and is not limited by the embodiments described herein, and is defined only by the claims set forth below.

[0033] Additionally, the terms used in this invention are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. Throughout the specification of this invention, the term 'comprising' any component means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0035] One aspect of the present invention is,

[0036] Serving with cerium oxide particles; and a solvent, wherein the cerium oxide particles have a primary particle size of 1 to 5 nm and a secondary particle size of 2 to 15 nm, and on the surface of the cerium oxide particles Ce 3+ and Ce 4+ A chemical mechanical polishing slurry composition is provided, characterized by containing [...].

[0037] Hereinafter, the chemical mechanical polishing slurry composition according to one aspect of the present invention will be described in detail.

[0038] FIG. 1 illustrates an oxide film removal mechanism according to an embodiment of the present invention. As shown in FIG. 1, Ce on the surface of ceria particles 3+ The ions must be activated to react smoothly with SiO2.

[0039] A chemical mechanical polishing slurry composition according to one aspect of the present invention comprises cerium oxide particles and a solvent.

[0040] The cerium oxide particles included as abrasive particles may have a positive zeta potential value, and preferably, the zeta potential value may be 10 to 50 mV. Since the zeta potential value of the cerium oxide particles is positive, the polarity of the silicon oxide film surface is negative, and the polishing efficiency is increased by the attractive force between the cerium oxide particles and the surface of the silicon oxide film, thereby suppressing the occurrence of a loading effect in which the initial polishing speed is slow in a pattern having a step.

[0041] Although the above cerium oxide particles have lower hardness compared to silica particles or alumina particles, the polishing speed of silicon-containing surfaces such as glass or semiconductor substrates is very fast due to the chemical polishing mechanism in which Si-O-Ce bonds are formed between silica and cerium, making it advantageous for polishing semiconductor substrates.

[0042] The cerium oxide particles may preferably have a primary particle size (TEM measurement) of 1 to 10 nm and a secondary particle size of about 25 nm or less. More preferably, the primary particle size may be 1 to 5 nm and the secondary particle size may be about 2 to 15 nm. Even more preferably, the primary particle size may be 1 to 4 nm and the secondary particle size may be about 2 to 12 nm. If the primary particle size of the cerium oxide is less than 1 nm, crystallinity is reduced and the polishing speed of the target film is inhibited, which may result in reduced polishing efficiency; conversely, if it exceeds 10 nm, there is a concern regarding surface defects such as scratches. Furthermore, in one embodiment of the present invention, the average primary particle size of the cerium oxide particles may be characterized as being 1 to 15 nm, preferably 1 to 12 nm, and more preferably 1 to 10 nm.

[0043] Accordingly, considering the appropriate polishing speed of the film to be polished and the dispersion stability within the slurry composition, the average particle size may be 1 to 20 nm. Preferably, the average particle size may be 2 to 15 nm, and more preferably, the average particle size may be 3 to 12 nm, specifically 3 to 10 nm.

[0044] The above cerium oxide primary particles may be one or more selected from the group consisting of cubic, tetragonal, orthorhombic, rhombohedral, monoclinic, hexagonal, triclinic, and cuboctahedron shapes, but preferably may be cubic, tetragonal, or orthorhombic in a rectangular or cubic shape, and more preferably may be cubic in a cubic shape.

[0045] According to one embodiment of the present invention, the cerium oxide particles may be manufactured by a method of growing particles through chemical synthesis, preferably using a bottom-up method. Methods such as the sol-gel method, supercritical reaction, hydrothermal reaction, or co-precipitation method may be used as the synthesis method for the cerium oxide particles, but are not limited thereto. The bottom-up method is a type of chemical synthesis that has recently gained attention, in which starting materials of atoms or molecules are grown into nanometer-sized particles through chemical reactions.

[0046] In the formation of secondary particles in abrasives, solvents each possess unique dielectric constant values. During powder synthesis, the dielectric constant of the solvent alters surface energy or surface charge during nucleation and crystal growth, thereby influencing the aggregation and growth of nuclei, which in turn affects the size and shape of the powder. The dielectric constant of the solvent and the surface potential (zeta potential) of particles dispersed within the solvent are proportional to each other; if the zeta potential is low, the surface repulsion between fine particles or between reaction-generated nuclei is small. Consequently, as this creates an unstable state, aggregation between fine particles or nuclei can occur at a very rapid rate. At this time, since the magnitude of the surface repulsion is similar for both fine particles and nuclei, aggregation to a uniform size becomes possible. Depending on reaction conditions such as temperature and concentration, these aggregated secondary particles undergo strong aggregation or particle merging processes, such as Ostwald ripening, to grow into relatively large particles.

[0047] The above cerium oxide particles may be included in an amount of 0.01 to 5 weight%, more preferably 0.03 to 3 weight%, and even more preferably 0.05 to 1 weight% based on the total chemical mechanical polishing slurry composition.

[0048] The cerium oxide particles of the present invention are distinguished from the abrasive particles of the prior art, Ce 3+ It exhibits Raman spectral features suggesting that the component is present in the chemical mechanical polishing slurry composition of the present invention. Specifically, the cerium oxide particles may be characterized by having two or more Raman peak spectra. This is Ce 4+ It is distinguished from conventional abrasives present on the surface of cerium oxide particles.

[0049] In one embodiment, the cerium oxide particles may have a spectrum of a first Raman peak within a band range of 455 cm-1 to 460 cm-1, a second Raman peak within a band range of 587 cm-1 to 627 cm-1, and a third Raman peak within a band range of 712 cm-1 to 772 cm-1.

[0050] In one embodiment, the ratio A / B of the first Raman peak intensity (A) to the second Raman peak intensity (B) may be characterized as being 35 or less, preferably A / B may be 30 or less, and more preferably A / B may be 25 or less. In addition, in one embodiment, the ratio A / C of the first Raman peak intensity (A) to the third Raman peak intensity (C) may be characterized as being 65 or less, preferably A / C may be 60 or less, and more preferably A / C may be 50 or less. As the values ​​of A / B and A / C satisfy the above ranges, Ce measured by the Raman peak spectrum 3+ / Ce 4+ The molar ratio can be 0.1 to 0.7, preferably 0.1 to 0.5.

[0051] In one embodiment, the aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt% may be characterized by having a light transmittance of 50% or more for light with a wavelength of 450 to 800 nm, preferably 70% or more, and more preferably 90% or more. The fact that the light transmittance satisfies the above range may mean that the primary particle size of the cerium oxide particles according to one embodiment of the present invention is small, and also that aggregation into secondary particles is less than that of conventional ceria particles.

[0052] The chemical mechanical polishing slurry composition may have a pH of 7 or lower, preferably 2 to 7, in terms of dispersion stability and polishing efficiency. More specifically, if the pH is less than 2, the removal rate of the silicon oxide film may decrease rapidly, resulting in undesirable polishing characteristics, and if the pH is greater than 7, undesirable polishing characteristics may be exhibited, or pH stability and dispersion stability may decrease, causing aggregation and resulting in micro-scratches and defects.

[0053] The chemical mechanical polishing slurry composition may include one or more acid or base pH adjusters and buffers capable of adjusting the pH by considering the final pH of the composition, polishing rate, polishing selectivity, etc. As for the pH adjuster for adjusting the pH, one capable of adjusting the pH without affecting the characteristics of the chemical mechanical polishing slurry composition may be used. Examples of acidic pH adjusters include inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid and citric acid. Examples of basic pH adjusters include sodium hydroxide, potassium hydroxide, ammonium hydroxide, and quaternary organic ammonium salts. The content of the pH adjuster may be appropriately adjusted by considering the final pH of the composition.

[0054] The above solvent may be any solvent used in a chemical mechanical polishing slurry composition, and for example, deionized water may be used, but the present invention is not limited thereto. Additionally, ultrapure water may preferably be used. The content of the solvent may be the remaining amount excluding the content of the cerium oxide particles and other additional additives with respect to the entire chemical mechanical polishing slurry composition.

[0055] The above slurry composition may include an additive capable of improving polishing efficiency. In a process of polishing a workpiece containing two or more different materials, the additive for improving polishing selectivity can selectively polish the other material with respect to one of the materials. As an example of the above additive, a quaternary ammonium compound, a lubricant, etc., may be additionally included as needed. The above quaternary ammonium compound may additionally provide a preservative function and a pH control function, and the amount used may be 0.01 to 10 weight%, preferably 0.1 to 5 weight%, of the total chemical mechanical polishing slurry composition. Examples of the above quaternary ammonium compound include ammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, or tetrabutylammonium hydroxide. The above lubricant is intended to assist in the lubricating function of the chemical mechanical polishing slurry composition, and may be used in an amount of 0.01 to 10 weight%, preferably 0.1 to 5 weight%, based on the total chemical mechanical polishing slurry composition.

[0056] The chemical mechanical polishing slurry composition described above has excellent dispersion stability and polishing selectivity, and in particular, has a high polishing rate for silicon oxide films and a low polishing rate for silicon nitride films, so it can be effectively used to selectively remove silicon oxide films from the surface of a semiconductor device in a CMP process, prioritizing silicon nitride films.

[0057] The chemical mechanical polishing slurry composition may be provided in the form of a one-component slurry composition containing all components such as cerium oxide particles, a solvent, and other additives, or, if necessary, in the form of a two-component or three-component slurry composition in which the components are stored separately in two or three or more containers and then mixed at or near the time of use. The selection of such forms of provision and the combination of stored components are within the knowledge of those skilled in the art, and the overall polishing characteristics and polishing speed can be adjusted by changing the mixing ratio.

[0059] Meanwhile, a method for manufacturing a semiconductor device according to another embodiment of the present invention includes a step of simultaneously polishing a barrier metal film, a silicon oxide film, and a silicon nitride film using the chemical mechanical polishing slurry composition. Through the polishing step, a through electrode can be formed. Any conventional polishing method and condition generally used for simultaneously polishing a barrier metal film, a silicon oxide film, and a silicon nitride film using the chemical mechanical polishing slurry composition can be used, and the present invention is not particularly limited. Therefore, a detailed description thereof is omitted in this specification.

[0061] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0063] Example 1. Preparation of a CMP slurry composition containing cerium oxide particles

[0064] Cerium oxide in an isometric form was prepared with a primary particle size of 1 to 5 nm and an average particle diameter of about 3 to 7 nm. The cerium oxide particles were manufactured by growing the particles through chemical synthesis using a bottom-up method. Chemical synthesis methods for cerium oxide particles may include the sol-gel method, supercritical reaction, hydrothermal reaction, and co-precipitation method, and all syntheses included ammonium-based additives to control the shape of the cerium particles.

[0065] A CMP slurry was prepared by adding cerium oxide particles having a predetermined particle size according to the present invention to deionized water to adjust the abrasive concentration to 0.1 wt%, and adding Ammonia as a pH adjuster to adjust the final pH to 5.5.

[0067] Comparative Example A.

[0068] A CMP slurry was prepared by adding conventional cerium oxide particles with an average particle size of 30 nm to deionized water to adjust the abrasive concentration to 0.05 wt%, and adding Ammonia as a pH adjuster to adjust the final pH to 5.5.

[0070] Comparative Example B.

[0071] Cerium oxide particles with an average particle size of 60 nm were prepared and added to deionized water to adjust the abrasive concentration to 0.05 wt%, and Ammonia was added as a pH adjuster to adjust the final pH to 5.5 to prepare a CMP slurry.

[0073] Experimental Example 1. XRD Analysis of Cerium Oxide Particles

[0074] Figure 2a shows the XRD analysis results of cerium oxide particles produced several times according to one embodiment of the present invention. The cerium oxide particles according to the present invention were analyzed using X-ray diffraction analysis (XRD, using Cu-Kα radiation with a wavelength of 0.154 nm at Rigaku DMAX 2500, 40 kV, and 100 mA).

[0075] All synthesized particles were confirmed to be pure cerium oxide, consistent with the standard JCPDS file (34-0394), and the grain size was measured through XRD patterns and found to be 2.8 to 3.5 nm in size.

[0076] Figure 2b compares the XRD analysis results of cerium oxide particles produced by the present invention and general cerium hydroxide particles.

[0078] Experimental Example 2. Analysis using Raman spectroscopy

[0079] Figure 4a shows the Raman peak spectrum results of conventional ceria particles with a particle size of 60 nm, Figure 4b shows the Raman peak spectrum results of cerium oxide particles prepared according to one embodiment of the present invention, and Figure 4c shows the comparison results of the Raman peak spectra of conventional ceria particles with a particle size of 60 nm and cerium oxide particles prepared according to one embodiment of the present invention.

[0080] Referring to Fig. 4a, in the case of a conventional slurry composition where Ce3+ is not present on the surface, 462 cm -1 While only the Raman peaks of are shown, referring to FIGS. 4b and 4c, the cerium oxide particles of the present invention show 457, 607, and 742 cm⁻¹. -1 It can be seen that the peaks are represented respectively. This is the peak in conventional ceria (462 cm⁻¹). -1 457cm at ) -1 It can be confirmed that a low shift occurred, and Ce 3+607cm due to large inclusion -1 , 742 cm -1 It can be confirmed that a peak has been generated.

[0081] In addition, in Tables 1 and 2 below, the respective Raman peak intensities of the cerium oxide particles of the present invention and 457 cm⁻¹ -1 / 607cm -1 and 457cm -1 / 742cm -1 The ratio of peak intensity between them was shown.

[0082] The present invention 457cm -1 Peak intensity at 607cm -1 Peak intensity at Approximately 457 cm -1 Peak intensity at approximately 607 cm -1 Ratio of peak intensities at No. 1 70244.7 3538.5 19.9 No. 2 75219.0 4394.8 17.1 No. 3 92824.5 4575.5 20.3 No. 4 87916.7 5403.3 16.3

[0083] The present invention 457cm -1 Peak intensity at 742cm -1 Peak intensity at Approximately 457 cm -1 Peak intensity at approximately 742 cm -1 Ratio of peak intensities at No. 1 70244.7 2861.75 24.54 No. 2 75219.0 1919.21 39.19 No. 3 92824.5 1981.58 46.84 No. 4 87916.7 3050.15 28.82

[0084] As shown in Tables 1 and 2 above, 457 cm -1 Peak intensity versus 607cm -1 Ratio of peak intensities and 457 cm -1 Peak intensity versus 607cm -1 As the ratio of peak intensities was found to be below a predetermined value, Ce 3+ It can be seen that the content is about 30~45%.

[0086] Experimental Example 3. Particle Size Analysis Using TEM / SEM

[0087] Figures 4a and 4b are TEM / SEM images of cerium oxide particles according to one embodiment of the invention. The primary particle size of cerium oxide particles according to Example 1 and Comparative Examples A and B was analyzed. Figure 4c shows the Malvern Zerasizer (DLS method) results of cerium oxide particles according to one embodiment of the invention, representing the secondary particle size results.

[0088] Referring to FIGS. 4a and 4b, it can be seen that the average size of the cerium oxide particles according to one embodiment of the present invention is about 4 nm, and the size of the secondary particles is about 10 nm (Fig. 4c). On the other hand, in the case of the conventional ceria particles of Comparative Examples A and B, the overall particle size was shown to be 20 nm or larger.

[0090] Experimental Example 4. Slurry Light Transmittance Analysis

[0091] Conventional ceria particles of Comparative Example A (or B) and cerium oxide particles according to one embodiment of the present invention were added to deionized water to adjust the abrasive concentration to 1.0 wt%, and a CMP slurry was prepared and the light transmittance was analyzed.

[0092] The optical spectrum was measured in the range of 200-800 nm using a UV-vis spectrophotometer (Jasco UV-vis spectrophotometer).

[0093] FIG. 5a shows the results of the light transmittance analysis of cerium oxide particles according to one embodiment of the present invention, and FIG. 6b shows the results of the light transmittance analysis according to the wavelength of cerium oxide particles according to one embodiment of the present invention.

[0094] According to Fig. 5a, in the case of the slurry containing conventional ceria particles, Comparative Example A, high turbidity could be observed even with the naked eye, whereas in the case of the slurry containing cerium oxide particles of the present invention, it was observed to be transparent, indicating high light transmittance.

[0095] Referring to FIG. 5b, it was confirmed that the light transmittance of the slurry according to the embodiment of the present invention was 97.4% or higher at wavelengths in the visible light region. This means that the primary particle size of the cerium oxide particles of the present invention is small, and the aggregation into secondary particles is less than that of conventional ceria particles.

[0097] Experimental Example 5. Evaluation of Polishing Characteristics

[0098] Polishing was performed using the CMP slurry compositions prepared in the above examples and Comparative Examples 1 and 2 according to the following polishing machine and polishing conditions, and the polishing rates for silicon oxide films (PETEOS silicon oxide films formed by plasma chemical vapor deposition) and silicon nitride films, as well as the polishing rate of polysilicon, were calculated, and the results are shown in Table 3 below.

[0099] Evaluation Equipment: Reflexion® LK CMP (Applied Materials)

[0100] Wafer: 300mm PETEOS Wafer

[0101] PAD: IC1010(DOW)

[0102] Grinding conditions: 2psi, Head: 65rpm, Platen: 67rpm, Flow rate: 200ml / min

[0103] Thin film measurement equipment: ST5000(K-Mac)

[0104] The slurry composition and polishing evaluation results are as shown in Table 2 below.

[0106] Comparative Example A Comparative Example B Examples Cerium oxide Commercially available 30nm nanoparticles Commercially available 60nm nanoparticles The particles of the present invention Ceria content 0.05% 0.05% 0.05% pH 5.5 5.5 5.5 PETEO removal rate 54 Å / min 546 Å / min 3,458 Å / min

[0107] Referring to Table 3 above, it can be seen that the embodiments of the present invention exhibit an excellent oxide film removal rate at a low content despite the small particle size.

[0108] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.

[0109] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and their equivalents should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A slurry composition for chemical mechanical polishing, comprising: cerium oxide particles; a pH adjuster; The aqueous dispersion comprising a solvent and the cerium oxide particles, with the cerium oxide particle content adjusted to 1.0 wt%, has an average light transmittance of 50% or more for wavelength light in the 450-800 nm region, the cerium oxide particles have a size of 2.8 to 3.5 nm as a result of measuring the grain size through an XRD pattern, the cerium oxide particles have a secondary particle size of 25 nm or less, the cerium oxide particles have a spectrum having a first Raman peak within a band range of 455 cm-1 to 460 cm-1, a second Raman peak within a band range of 587 cm-1 to 627 cm-1, and a third Raman peak within a band range of 712 cm-1 to 772 cm-1, the ratio A / B of the first Raman peak intensity (A) to the second Raman peak intensity (B) is 25 or less, and the ratio of the first Raman peak intensity (A) to the third Raman peak intensity (C) A chemical mechanical polishing slurry composition characterized by a ratio of A / C of 50 or less and being transparent when observed with the naked eye. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 In claim 1, Ce on the surface of the cerium oxide particles 3+ A chemical mechanical polishing slurry composition characterized by containing 30% or more of Claim 8 delete Claim 9 A chemical mechanical polishing slurry composition according to claim 1, characterized in that the aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 weight% has an average light transmittance of 90% or more for wavelength light in the 800 nm region. Claim 10 A chemical mechanical polishing slurry composition according to claim 1, characterized in that the cerium oxide particles are included in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the total composition. Claim 11 A chemical mechanical polishing slurry composition according to claim 1, characterized in that the pH of the composition is 2 to 7. Claim 12 delete Claim 13 A method for manufacturing a semiconductor device comprising the step of polishing using a chemical mechanical polishing slurry composition according to claim 1. Claim 14 delete

Citation Information

Patent Citations

  • Cerium oxide slurry for polishing semiconductor thinlayer and preparation thereof

    KR1020050029605A

  • Method for producing cerium oxide particles, cerium oxide particles produced through same, and polishing slurry including same

    KR1020150024876A

  • Slurry comprising for sti polishing

    KR1020170004462A

  • Polishing composition containing ceria particles and method of use

    KR1020170125379A

  • Composition for performing material removal operation and method for forming the same

    KR1020200067835A